2002
DOI: 10.1177/070674370204701008
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Medication during Pregnancy and Lactation in Women with Schizophrenia: Evaluating the Risk

Abstract: Research is needed so that physicians may more accurately inform women about the relative risks of using antipsychotic medications during pregnancy and lactation. Increased knowledge about the risks of medication exposure will allow clinicians to limit treatment to situations in which the risk of untreated maternal illness outweighs the risk of exposing a developing infant to medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 59 publications
(37 reference statements)
1
32
0
6
Order By: Relevance
“…Data regarding phenothiazines are less consistent. A meta-analyses has found that first trimester exposure to phenothiazines may be associated with a slight increase in relative risk of fetal anomalies in some women with schizophrenia (65).…”
Section: Antipsychotic Agentsmentioning
confidence: 99%
“…Data regarding phenothiazines are less consistent. A meta-analyses has found that first trimester exposure to phenothiazines may be associated with a slight increase in relative risk of fetal anomalies in some women with schizophrenia (65).…”
Section: Antipsychotic Agentsmentioning
confidence: 99%
“…The risk of using antipsychotic medications during antenatal period and on breast feeding remains uncertain. There is not clear if antipsychotic drugs are associated with major malformations [41].…”
Section: Schizophreniamentioning
confidence: 99%
“…Women with schizophrenia may discontinue their medications when trying to conceive or upon discovering they are *Address correspondence to this author at the Comprehensive Family Care Center, Montefiore Medical Center, 1621 Eastchester Road, Bronx, NY 10461, USA; Tel: (718) 405-8267; Fax: (718) 405-8050; E-mail: afrieder@montefiore.org pregnant, rendering them vulnerable to an exacerbation or relapse of their illness during pregnancy [4][5][6]. Psychosis during pregnancy is of great concern as it can lead to fetal distress, denial of pregnancy, failure to participate in prenatal care, and/or failure to recognize the signs of labor [6][7][8].…”
Section: Preconception Carementioning
confidence: 99%
“…The risks of untreated mental illness on the pregnancy need to be weighed against the risks of the psychotropics the woman may be taking [3,5,6]. Risk/benefit assessment and decision with respect to treatment should be individualized on a case-by-case basis.…”
Section: Reproductive Decisionsmentioning
confidence: 99%